Walkability and its association with prevalent and incident diabetes among adults in different regions of Germany: results of pooled data from five German cohorts - Kartschmit, Nadja; Sutcliffe, Robynne; Sheldon, Mark Patrick; Moebus, Susanne; Greiser, Karin Halina; Hartwig, Saskia; Thürkow, Detlef; Stentzel, Ulrike; Berg, Neeltje van den; Wolf, Kathrin; Maier, Werner; Peters, Annette; et al. (BMC endocrine disorders, 2020)
Built environment, Walkability, Diabetes, Cardio-metabolic risk factors, Epidemiology